Five-Year Prospective Study on Implant Failure and Marginal Bone Remodeling Expected Using Bone Level Implants with Sandblasted/Acid-Etched Surface and Conical Connection - Tallarico, Marco; Lumbau, Aurea Maria Immacolata; Meloni, Silvio Mario; Ieria, Irene; Park, Chang-Joo; Zadrożny, Lukasz; Xhanari, Erta; Pisano, Milena (European Journal of Dentistry, 2022)
Objective The purpose of the present prospective, case-series study was to report implant survival rate and marginal bone remodeling expected 5 years after loading using dental implants placed in daily practice.Materials and Methods This research was designed as an open-cohort, prospective, case-series evaluation. Any partially or completely edentulous patient, scheduled to receive at least one bone level implant, was considered eligible for this study. Primary outcome measurements were: implant and prosthetic cumulative survival rate and any complications experienced up to the 5-year follow-up. Secondary outcome measures were: thickness of gingival biotype, implant insertion torque, implant stability quotient, and marginal bone loss (MBL).Results Ninety consecutive patients (34 males and 56 females, aged between 24 and 81 years old [mean: 53.2 ± 15.4]) with 243 inserted implants were followed for at least 5 years after loading (mean: 65.4 ± 3.1 months; range from 60 to 72). At the 1-year follow-up, no drop-outs were recorded, but 17 patients (18.9%) with 18 restorations (12.6%) delivered on 34 implants (14%) were lost at the 5-year examination. At the 5-year follow-up examination, six implants lost osseointegration (97.5%). In the same period, four prostheses failed (97.2%). Five complications were reported in five different patients (prosthetic success rate was 96.5%, at patient level). Five years after loading, the mean MBL was 0.41 ± 0.30 mm. The difference from the 1-year data was 0.04 ± 0.19 mm. A statistically significant higher MBL was found for smokers, and patients with thin gingival biotype. The mean implant insertion torque was 42.9 ± 4.8 Ncm (range from 15 to 45 Ncm). Two-hundred and three implants (83.5%) were inserted with an insertion torque ≥35 and ≤45 Ncm.Conclusions High implant survival and success rate could be expected with stable marginal bone remodeling up to 5 years after loading. Smoking and thin tissue biotype were the most important variabilities associated with higher MBL. Further research studies are needed to confirm these results.
Keywords: sandblasted; acid-etched; connection; marginal bone remodeling; marginal bone loss